Analisis Dan Perancangan Sistem Informasi Administrasi Penerbitan Akta Kelahiran Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Jambi - Saputra, Abdi; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2020)
In the research conducted at the Department of Population and Civil Registration of Jambi City, namely analyzing the current system, researchers found problems related to the birth certificate submission process there are several problems with the current system, the process of filing a birth certificate that runs on the Department of Population and Civil Registration Jambi City is still manual, meaning that people who want to submit a birth certificate application must be known by the Rukun Tetangga (RT) and the Kelurahan, after which the applicant submits the file to the Jambi City Population and Civil Registration Officer. Then it needs a system that can solve weaknesses or problems that occur. The researcher tried to make alternative problem solving in overcoming the weaknesses of the Birth Certificate Administration Information System that made it easier for the community in the process of submitting a birth certificate. This research uses UML (Modeling Language) Language modeling.